الامام ابن عبد البر واختياراته الفقهية من خلال كتابه الاستذكار- كتاب القران نموذجا- - بونجيم, علي; بن عمر, عبد المجيد; قدة, يحي (University of Eloued-جامعة الوادي, 2014)
This research aims to highlight a character Giants adults in Islamic Sciences: YOUCEF BEN ABDELBAR ENAMRI; Where it is sincere in the request until he reached the peak of science and especially modern sciences and Islamic Jurisprudence, readings, novels, language, history and genealogy, literature, and managed to occupy a valuable niche in the hearts of scientists. And so by definition al-istithkar his book which is one of the best explanations Muwatta, and the first author combines Quran and Hadith, He dealt with the issues of the disputed among scholars methodology of comparative jurisprudence, and we - God willing - in this study modest We had one example of one of the doors of jurisprudence which Kitab Qur'an; where we found great attention the Qur'an and its Sciences, shows that in matters of practical operation indicates the choices of jurisprudence approved the inference of the evidence and religious texts, and derived from the principles and rules and doctrinal fundamentalism represents a scientific approach taken by Imam access to legal judgment without prejudice to the doctrine
مذكرة ليسانس
Keywords: كتاب القران/ كتاب الاستذكار /الاختيارات الفقهية; Le livre du Coran/livre de souvenir/choix jurisprudentiels